A Study of Deming Quality Cycle Model Affecting Employee Performance Management - Juanjuan, Lei (Science, Technology, and Social Sciences Procedia, 2024)
In 2020, affected by the severe economic situation at home and abroad, coupled with the sudden outbreak of the novel coronavirus, the challenges and risks faced by China’s banking industry will increase sharply, and the risks faced by the banking industry will become increasingly large, which puts higher requirements on the risk identification ability, management level and control technology of commercial banks. This study uses Deming quality cycle model as research method to study how to optimize the employee performance management process of Z Bank. The sample of this paper is 303 persons randomly selected from 14.30 middle, senior and junior employees of the management of Z Bank. The research tool was questionnaire, and the content validity and reliability of the questionnaire were 0.78 and 0.85, respectively. Statistics used for data analysis include percentages, averages, and standard deviations. Follow-up analysis was conducted according to the average of statistical results. The results show that: In the performance planning survey of Z Bank, the comprehensive scores of Z bank employees in the performance stages of Plan, Do, Check, Action and overall performance process are 3.21, 2.65, 2.55, 2.48 and 2.42, respectively. The grades are Middle, Middle, Middle, Low, Low. The results show that there are problems that need to be optimized in every stage, and the performance of planning stage is better than other stages. It can be seen that the current Z bank needs to optimize the existing performance evaluation system, focusing on the 3 stages of Action, Check and Do. The overall fitting R-square value of the model is 0.664, indicating that the overall fitting of the model is good. Each variable is significant at least at the 5 % level (the p-value of all 4 variables is less than 5 %, that is, less than 0.05).